Improve Student Learning Environment with MyClassRoom (MCR) and Cloud Storage Collaboration - Rijois I. E. Saragih (Geviva Publisher, 2023)
Pandemic has changed the process of education in the world, it leads to a better approach of learning through an online environment. Unfortunately, most educational institutions are still using conventional approaches in their learning system, in fact, information technology has been growing continuously nowaday, especially mobile applications. This paper presents a collaboration between myclassroom application and google drive to improve student learning environment, especially in providing materials, attendance, assignments and grades based on mobile. This study used a design-based research methodology with a waterfall application development process and a questionnaire to collect feedback from one hundred and twenty-one students on the features and content of myclassroom. The myclassroom application was successfully developed using the Model View Controller concept with databases and google drive collaboration. The application testing has confirmed that myclassroom has been successfully developed and works properly. The result shows that the student learning environment has improved by up to 95%.